PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN, DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PARUH WAKTU PADA CV. KARYA GEMILANG “NCO EVENT ORGANIZER” - Arya Munang Ayu Heny Ratna Dewi; I Nengah Suardhika; I Gede Yudhi Hendrawan (EMAS, 2021)
Success in the company is determined by the achievement of good performance results by employees. Human resources in a company greatly affect the company's performance, because if the human or employee's performance is good, then the company's performance will be good. Conversely, if the performance of people or employees in a company decreases, the company's performance will also decline. This study aims, to determine and explain individual characteristics, job characteristics and organizational climate on the performance of part-time employees at CV. Karya Gemilang "NCO Event Organizer". The number of samples in this study were as many as 36 employees, sampling using the census method. The collected data were analyzed using multiple linear regression. The results of the analysis show that individual characteristics have a positive and significant effect on employee performance, job characteristics have a positive and significant effect on employee performance, organizational climate has a positive and significant effect on employee performance.